Perspective: rethinking therapeutic strategies in oncology - Patz, Edward F.; Gottlin, Elizabeth B.; Simon, George R. (Frontiers in Oncology, 2024)
Immuno-oncology has revolutionized cancer care, drug development, the design of clinical trials, standard treatment paradigms, and the evaluation of response to therapy. These are all areas, however, that have not fully incorporated principles of tumor immunology. Insufficient emphasis is put on the effect drugs have on the immune system, and specifically, the impact that multiple lines of therapy can have on the functioning of the immune system, hindering a robust anti-tumor immune response. A paradigm shift in how we approach the development of novel immunotherapeutic agents is necessary to facilitate the effective improvements in patient outcomes.